Imágenes, lengua y creencias en Lusitania romana - García, Jorge Tomás; Prete, Vanessa Del (Access archaeology., 2019)
The papers in this volume consider the visual, linguistic and religious culture of the Roman province of Lusitania (modern Portugal (south of the Douro river) and part of western Spain).